Cross Cultural Differences in Cognition: A Study on How Culture Affects the Way We Think - Sharon Campbell- Phillips; Deb Proshad Halder; Serlange Campbell; Daneil Phillips (SIASAT, 2020)
Communication is the exchanging of information through speaking, writing and signals. It plays an important to our development; it is the dissemination of ideas, and information to persons. Cognition is our mental process in which we acquire knowledge and understanding, and this is done through our thoughts, our experiences, and our senses. Cultural differences involve what people’ believe how they behave, the language they speak, and their practices based on their ethnicity. Cross-cultural differences in cognition can be very effective to certain operations conducted by persons; however, it can also limit us based on our perspective. To gather information and to understand how culture affects cognition and the way we think, questionnaires, surveys and experiments were used. Questionnaires were administered to tertiary level students, surveys were administered to teachers and experiments were conducted among students from various culture and background. The experiments were centered on visualization, focus and critical thinking. The purpose of this study is to investigate if cultural differences affect the way we think, and this double-dissociation is discussed in terms of implications for different developmental trajectories, with different developmental sub-tasks in the different cultures.